Acid-base composite high-temperature proton exchange membrane as well as preparation method and application thereof
By using carboxyl-containing hydrogen bond organic frame material with polybenzimidazole for acid-base crosslinking and soaking in high-temperature proton exchange membranes, the problem of improving proton conduction performance and mechanical strength is solved, the loss of phosphoric acid is slowed down, and the loss of phosphoric acid is improved. Battery stability.
Patent Information
- Application Number
- CN202310952078.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-31
AI Technical Summary
The existing high-temperature proton exchange membrane fuel cells have challenges in improving proton conduction performance and mechanical strength, and the loss of phosphoric acid is difficult to overcome.
The hydrogen bond organic frame material containing carboxyl groups is used to crosslink acid-base with polybenzimidazole, and soak through phosphoric acid to form a crosslinked hydrogen bond network, which improves mechanical strength and increases the phosphoric acid load and proton conductivity through high specific surface area. .
The mechanical strength and proton conduction performance of the high-temperature proton exchange membrane are achieved while improving, which slows down the loss of phosphoric acid and improves the battery operation stability.
Smart Images

Figure CN119432069A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an acid-base composite high-temperature proton exchange membrane and a preparation method and application thereof, belonging to the fields of new material technology and new energy technology. Background Art
[0002] Hydrogen energy is a renewable and clean energy source that will gradually replace the increasingly depleted fossil energy and become an important part of the world's energy structure. Fuel cells can convert hydrogen energy into electrical energy, so they have attracted widespread attention. Proton exchange membrane fuel cells with proton exchange membrane as electrolyte have the characteristics of high energy conversion efficiency, low operating temperature, fast startup, and long life. They can be widely used as power sources for vehicles and fixed power stations. They are currently the fuel cells with the most promising commercial applications. At present, proton exchange membrane fuel cells have problems such as low environmental adaptability, low utilization efficiency of precious metal catalysts, high cost, and complex water and heat management systems. It is generally believed that increasing the operating temperature of fuel cells is an effective countermeasure to solve these problems. When the operating temperature of the proton exchange membrane fuel cell is increased above 100°C, the battery reaction kinetics will increase, the catalytic efficiency of the Pt catalyst will increase, and the use of the Pt catalyst can be greatly reduced; and the tolerance of the Pt catalyst to CO also increases exponentially with temperature; at the same time, increasing the operating temperature will reduce the battery's requirements for the water and heat management system. However, too high a temperature (above 500°C) will place more stringent requirements on the component materials of the proton exchange membrane fuel cell. Therefore, the development of high temperature (100-500℃) proton exchange membrane fuel cells is of great significance. The most important challenge in the development of high temperature proton exchange membrane fuel cells is to develop a high temperature proton exchange membrane with superior performance.
[0003] In view of the unique advantages of high-temperature proton exchange membrane fuel cells, research on high-temperature proton exchange membranes has become a hot topic. Among them, polybenzimidazole is widely used in the field of high-temperature fuel cell proton exchange membranes due to its excellent thermal stability and mechanical strength. Since polybenzimidazole itself has a very weak ability to transport protons, it is necessary to modify polybenzimidazole. One of the main methods is to improve the proton transport capacity by doping polybenzimidazole with phosphoric acid, mainly by immersing the polybenzimidazole membrane in phosphoric acid. However, its proton conductivity and mechanical strength have always been in a trade-off problem, and further improvement of battery performance is difficult to achieve, and the loss of phosphoric acid has been difficult to overcome. Therefore, under the premise of ensuring the thermal stability and dimensional stability of the proton exchange membrane, how to improve its mechanical properties and proton conductivity at the same time is an urgent problem to be solved in terms of application. Summary of the invention
[0004] According to one aspect of the present application, an acid-base composite high-temperature proton exchange membrane is provided, wherein the acid-base composite high-temperature proton exchange membrane is formed by acid-base cross-linking of a carboxyl-containing hydrogen-bonded organic framework material and polybenzimidazole, and then soaking in phosphoric acid;
[0005] The carboxyl-containing hydrogen-bonding organic framework material is selected from one of the structures shown in Formula I-1, Formula I-2, Formula I-3, and Formula I-4;
[0006]
[0007]
[0008] Optionally, the mass ratio of the carboxyl-containing hydrogen-bonding organic framework material to polybenzimidazole is 3:97 to 21:79.
[0009] Optionally, the mass ratio of the carboxyl-containing hydrogen-bonding organic framework material to polybenzimidazole is selected from any value of 3:97, 5:95, 7:93, 9:91, 11:89, 13:87, 15:85, 17:83, 19:81, 21:79 or a range between any two of the above.
[0010] The appropriate ratio can make the carboxyl-containing hydrogen-bonded organic framework material evenly dispersed in polybenzimidazole, and form a cross-linked hydrogen bond network under the acid-base interaction with polybenzimidazole, thereby improving the mechanical strength; at the same time, with the help of the high specific surface area of the hydrogen-bonded organic framework material, the phosphate loading capacity is increased, promoting the stable, uniform and efficient transmission of protons, thereby improving proton conductivity and battery performance.
[0011] According to another aspect of the present application, a method for preparing the above-mentioned acid-base composite high-temperature proton exchange membrane is provided, and the preparation method comprises the following steps:
[0012] (1) ultrasonically dispersing a mixture of a carboxyl-containing hydrogen-bonded organic framework material, polybenzimidazole, and a solvent to obtain a casting solution;
[0013] (2) The cast membrane is hydraulically pressed onto the surface of the substrate by a doctor blade method, dried, and soaked in phosphoric acid to obtain the acid-base composite high-temperature proton exchange membrane.
[0014] Optionally, in the casting solution, the sum of the mass fractions of the carboxyl-containing hydrogen-bonding organic framework material and polybenzimidazole is 2.5-10%.
[0015] Optionally, the sum of the mass fractions of the carboxyl-containing hydrogen-bonding organic framework material and the polybenzimidazole is selected from any value of 2.5%, 4%, 5.5%, 7%, 8.5%, 10% or a range between any two of the above.
[0016] Optionally, the solvent is selected from at least one of N,N-dimethylacetamide, N,N-dimethylformamide and dimethyl sulfoxide.
[0017] Optionally, the solvent is selected from N,N-dimethylacetamide (DMAC) and / or dimethyl sulfoxide (DMSO).
[0018] In the present application, N,N-dimethylacetamide (DMAC) and dimethyl sulfoxide (DMSO) have better dispersibility for carboxyl-containing hydrogen-bonded organic framework materials and polybenzimidazole, and can be dispersed more easily.
[0019] Optionally, the ultrasonic dispersion time is 4 to 12 hours.
[0020] Optionally, the substrate is a glass substrate.
[0021] Optionally, the drying temperature is 50-80°C.
[0022] Optionally, the drying temperature is selected from any value of 50°C, 60°C, 70°C, 80°C or a range between any two of the above values.
[0023] Optionally, the soaking temperature is 60-100° C., and the soaking time is 2-4 days.
[0024] Optionally, the soaking temperature is selected from any value of 60°C, 70°C, 80°C, 90°C, 100°C or a range between any two of the above values.
[0025] Optionally, the soaking time is selected from any value among 2 days, 2.5 days, 3 days, 3.5 days, 4 days, or a range between any two of the above.
[0026] According to another aspect of the present application, there is provided an application of the above-mentioned acid-base composite high-temperature proton exchange membrane in a fuel cell, wherein the working temperature of the acid-base composite high-temperature proton exchange membrane is 100-200°C.
[0027] Optionally, the novel acid-base composite high-temperature proton exchange membrane is used in fuel cells at an applicable temperature of 100 to 200°C.
[0028] In the present application, the composite high-temperature proton exchange membrane has a polybenzimidazole membrane and a carboxyl-containing hydrogen-bonding organic framework material as its skeleton. The carboxyl-containing hydrogen-bonding organic framework material contains carboxyl sites and can undergo acid-base cross-linking with polybenzimidazole; at the same time, it stores and binds phosphate molecules through hydrogen bonding and ultra-high specific surface area.
[0029] The carboxyl group of the hydrogen-bonded organic framework material in the present application can undergo acid-base crosslinking with polybenzimidazole, thereby improving the mechanical strength of the composite membrane; at the same time, the hydrogen-bonded organic framework material provides a huge storage space for phosphoric acid molecules due to its ultra-high specific surface area; in addition, the abundant hydrogen bonds in the hydrogen-bonded organic framework material also provide additional binding force for the phosphoric acid molecules, thereby improving the proton conduction performance and phosphoric acid stability of the composite membrane. Introducing the carboxyl-containing hydrogen-bonded organic framework material in the present invention into the composite membrane not only improves the mechanical strength of the composite membrane, but also improves the proton conduction performance, slows down the loss of phosphoric acid, and improves the battery operation stability. The resulting composite proton exchange membrane is extremely dense and has a strong proton conduction capacity.
[0030] The beneficial effects of this application include:
[0031] 1) The present application introduces a hydrogen-bonded organic framework material having a carboxyl group into polybenzimidazole, and the hydrogen-bonded organic framework material having a carboxyl group undergoes acid-base crosslinking with the polybenzimidazole, thereby forming an effective crosslinking network in the composite film and improving the mechanical strength of the composite film.
[0032] 2) The hydrogen-bonded organic framework material provided in the present application provides a huge storage space for phosphoric acid molecules due to its ultra-high specific surface area, thereby improving the proton conduction performance of the composite membrane.
[0033] 3) The abundant hydrogen bonds in the hydrogen-bonded organic framework material provided in the present application provide additional binding force for the phosphoric acid molecules, slowing down the loss rate of phosphoric acid in the composite membrane and improving the battery operation stability, and has great application potential in the field of high-temperature fuel cell proton exchange membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The curves showing the change of proton conductivity of the high temperature proton exchange membrane with temperature in Examples 1 to 6 and Comparative Examples 1 to 2 of the present application.
[0035] Figure 2 This is a graph showing the phosphoric acid retention rate of the high temperature proton exchange membrane in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0036] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0037] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0038] A high-precision balance was used to test the phosphoric acid absorption rate of the high-temperature proton exchange membrane;
[0039] The tensile strength of high temperature proton exchange membrane is tested using a universal testing machine;
[0040] The elongation at break of high temperature proton exchange membrane was tested using a universal testing machine.
[0041] The proton conductivity of the high-temperature proton exchange membrane was tested using an electrochemical workstation.
[0042] In the examples of the present application, room temperature refers to "25°C".
[0043] A method for preparing a composite high-temperature proton exchange membrane, the preparation method comprising the following steps:
[0044] 1) mixing the carboxyl-containing hydrogen-bonded organic framework material and polybenzimidazole in a solvent and uniformly dispersing them by ultrasonication to obtain a film casting solution;
[0045] 2) dropping the casting liquid onto the substrate, and evenly pressing the casting liquid onto the surface of the substrate by a doctor blade method;
[0046] 3) transferring the substrate to a vacuum oven to promote solvent volatilization to obtain a composite film;
[0047] 4) The composite membrane is immersed in a phosphoric acid solution to obtain a novel acid-base composite high-temperature proton exchange membrane.
[0048] Example 1
[0049] A method for preparing a composite high-temperature proton exchange membrane comprises the following steps:
[0050] 1) Dispersing 0.16 g of carboxyl-containing hydrogen-bonded organic framework material formula I-2 in 4 g of N,N-dimethylacetamide, and ultrasonically dispersing for 1 hour to obtain dispersion A; dispersing 0.84 g of polybenzimidazole in 15 g of N,N-dimethylacetamide, and ultrasonically dispersing for 1 hour to obtain dispersion B; mixing dispersions A and B, and stirring at room temperature for 24 hours to obtain a casting solution;
[0051] 2) dropping the casting liquid onto the glass substrate, and evenly pressing the casting liquid onto the surface of the substrate by a doctor blade method;
[0052] 3) transferring the substrate to a vacuum oven at 80°C to promote the evaporation of the solvent and obtain a composite film;
[0053] 4) The composite membrane is immersed in a phosphoric acid solution at 80° C. for 2 days to obtain a novel acid-base composite high-temperature proton exchange membrane.
[0054] Example 2
[0055] A method for preparing a composite high-temperature proton exchange membrane comprises the following steps:
[0056] 1) Dispersing 0.05 g of carboxyl-containing hydrogen-bonded organic framework material formula I-3 in 4 g of N,N-dimethylformamide, and ultrasonically dispersing for 1 h to obtain dispersion A; dispersing 0.95 g of polybenzimidazole in 15 g of N,N-dimethylacetamide, and ultrasonically dispersing for 1 h to obtain dispersion B; mixing dispersions A and B, and stirring at room temperature for 24 hours to obtain a casting solution;
[0057] 2) dropping the casting liquid onto the glass substrate, and evenly pressing the casting liquid onto the surface of the substrate by a doctor blade method;
[0058] 3) transferring the substrate to a 60°C vacuum oven to promote solvent evaporation and obtain a composite film;
[0059] 4) The composite membrane is immersed in a phosphoric acid solution at 60° C. for 4 days to obtain a novel acid-base composite high-temperature proton exchange membrane.
[0060] Example 3
[0061] A method for preparing a composite high-temperature proton exchange membrane comprises the following steps:
[0062] 1) Dispersing 0.10 g of carboxyl-containing hydrogen-bonded organic framework material formula I-4 in 2 g of dimethyl sulfoxide, and ultrasonically dispersing for 1 h to obtain dispersion A; dispersing 0.90 g of polybenzimidazole in 7 g of dimethyl sulfoxide, and ultrasonically dispersing for 1 h to obtain dispersion B; mixing dispersions A and B, and stirring at room temperature for 24 hours to obtain a casting solution;
[0063] 2) dropping the casting liquid onto the glass substrate, and evenly pressing the casting liquid onto the surface of the substrate by a doctor blade method;
[0064] 3) transferring the substrate to a 50°C vacuum oven to promote solvent evaporation and obtain a composite film;
[0065] 4) The composite membrane is immersed in a phosphoric acid solution at 100° C. for 2 days to obtain a novel acid-base composite high-temperature proton exchange membrane.
[0066] Example 4
[0067] A method for preparing a composite high-temperature proton exchange membrane comprises the following steps:
[0068] 1) Dispersing 0.12 g of carboxyl-containing hydrogen-bonded organic framework material formula I-1 in 10 g of N,N-dimethylformamide, and ultrasonically dispersing for 1 hour to obtain dispersion A; dispersing 0.88 g of polybenzimidazole in 29 g of dimethyl sulfoxide, and ultrasonically dispersing for 1 hour to obtain dispersion B; mixing dispersions A and B, and stirring at room temperature for 24 hours to obtain a casting solution;
[0069] 2) dropping the casting liquid onto the glass substrate, and evenly pressing the casting liquid onto the surface of the substrate by a doctor blade method;
[0070] 3) transferring the substrate to a vacuum oven at 80°C to promote the evaporation of the solvent and obtain a composite film;
[0071] 4) The composite membrane is immersed in a phosphoric acid solution at 100° C. for 2 days to obtain a novel acid-base composite high-temperature proton exchange membrane.
[0072] Example 5
[0073] A method for preparing a composite high-temperature proton exchange membrane comprises the following steps:
[0074] 1) Dispersing 0.03 g of carboxyl-containing hydrogen-bonded organic framework material formula I-2 in 5 g of N,N-dimethylformamide, and ultrasonically dispersing for 1 h to obtain dispersion A; dispersing 0.97 g of polybenzimidazole in 14 g of dimethyl sulfoxide, and ultrasonically dispersing for 1 h to obtain dispersion B; mixing dispersions A and B, and stirring at room temperature for 24 hours to obtain a casting solution;
[0075] 2) dropping the casting liquid onto the glass substrate, and evenly pressing the casting liquid onto the surface of the substrate by a doctor blade method;
[0076] 3) transferring the substrate to a vacuum oven at 80°C to promote the evaporation of the solvent and obtain a composite film;
[0077] 4) The composite membrane is immersed in a phosphoric acid solution at 100° C. for 2 days to obtain a novel acid-base composite high-temperature proton exchange membrane.
[0078] Example 6
[0079] A method for preparing a composite high-temperature proton exchange membrane comprises the following steps:
[0080] 1) Dispersing 0.21 g of carboxyl-containing hydrogen-bonded organic framework material formula I-2 in 5 g of N,N-dimethylformamide, and ultrasonically dispersing for 1 h to obtain dispersion A; dispersing 0.79 g of polybenzimidazole in 14 g of dimethyl sulfoxide, and ultrasonically dispersing for 1 h to obtain dispersion B; mixing dispersions A and B, and stirring at room temperature for 24 hours to obtain a casting solution;
[0081] 2) dropping the casting liquid onto the glass substrate, and evenly pressing the casting liquid onto the surface of the substrate by a doctor blade method;
[0082] 3) transferring the substrate to a vacuum oven at 80°C to promote the evaporation of the solvent and obtain a composite film;
[0083] 4) The composite membrane is immersed in a phosphoric acid solution at 100° C. for 2 days to obtain a novel acid-base composite high-temperature proton exchange membrane.
[0084] Comparative Example 1
[0085] A method for preparing a high-temperature proton exchange membrane, which differs from Example 1 only in that no carboxyl-containing hydrogen-bonding organic framework material is added, specifically comprising the following steps:
[0086] 1) Dispersing 1.0 g of polybenzimidazole in 19 g of N,N-dimethylacetamide, ultrasonically dispersing for 1 h, and stirring at room temperature for 24 hours to obtain a casting solution;
[0087] 2) dropping the casting liquid onto the glass substrate, and evenly pressing the casting liquid onto the surface of the substrate by a doctor blade method;
[0088] 3) Transfer the substrate to a vacuum oven at 80°C to promote solvent evaporation;
[0089] 4) The membrane is immersed in a phosphoric acid solution at 80° C. for 2 days to obtain a high-temperature proton exchange membrane.
[0090] Comparative Example 2
[0091] A method for preparing a high-temperature proton exchange membrane, which differs from Example 4 only in that no carboxyl-containing hydrogen-bonding organic framework material is added, specifically comprising the following steps:
[0092] 1) 1.0 g of polybenzimidazole was dispersed in 39 g of dimethyl sulfoxide, ultrasonically dispersed for 1 h, and stirred at room temperature for 24 h to obtain a casting solution;
[0093] 2) dropping the casting liquid onto the glass substrate, and evenly pressing the casting liquid onto the surface of the substrate by a doctor blade method;
[0094] 3) Transfer the substrate to a vacuum oven at 80°C to promote solvent evaporation;
[0095] 4) The membrane is immersed in a phosphoric acid solution at 100° C. for 2 days to obtain a high-temperature proton exchange membrane.
[0096] Performance Test 1
[0097] The phosphate absorption rate, tensile strength, and elongation at break of the high temperature proton exchange membranes of Examples 1 to 6 and Comparative Examples 1 to 2 were tested respectively (the test object was the composite membrane obtained in step 3). The test results are shown in Table 1.
[0098] Table 1
[0099] Examples Phosphoric acid absorption rate / % Tensile strength / MPa Elongation at break / % Example 1 352.1 157.9 5.29 Example 2 310.9 135.2 4.82 Example 3 325.2 141.6 5.02 Example 4 332.9 149.8 5.12 Example 5 301.5 124.8 4.69 Example 6 321.2 152.8 4.36 Comparative Example 1 281.6 121.6 4.25 Comparative Example 2 252.7 112.0 3.98
[0100] Performance Test 2
[0101] The tensile strength and elongation at break of the high temperature proton exchange membranes of Examples 1 to 6 and Comparative Examples 1 to 2 (the test object is the proton exchange membrane obtained in step 4)) were tested respectively. The test results are shown in Table 2.
[0102] Table 2
[0103] Examples Tensile strength / MPa Elongation at break / % Example 1 35.8 126.9 Example 2 28.6 110.2 Example 3 30.9 116.4 Example 4 32.1 121.2 Example 5 27.2 101.8 Example 6 30.2 102.9 Comparative Example 1 26.9 97.6 Comparative Example 2 23.7 92.1
[0104] Performance Test 3
[0105] The proton conductivity curves of the high temperature proton exchange membranes in Examples 1 to 6 and Comparative Examples 1 to 2 were tested as a function of temperature (the test object was the proton exchange membrane obtained in step 4). The test results are shown in FIG. Figure 1 shown.
[0106] From Table 1, Table 2 and Figure 1 It can be seen that the composite high-temperature proton exchange membrane provided by the present application improves the phosphoric acid absorption rate, thereby improving the proton conductivity; at the same time, due to the acid-base cross-linking interaction, the dimensional stability of the composite membrane is greatly improved, thereby improving the mechanical strength. From the comparison of Example 6 and Example 1, it can be seen that as the mass ratio of the carboxyl-containing hydrogen-bonded organic framework material to polybenzimidazole increases to a certain extent, the hydrogen-bonded organic framework material is prone to agglomeration, resulting in a decrease in membrane quality, thereby affecting the phosphoric acid absorption rate, proton conductivity and mechanical strength.
[0107] Performance Test 4
[0108] The phosphate rejection rates of the high temperature proton exchange membranes prepared in Example 1 and Comparative Example 1 were tested respectively (the test object was the proton exchange membrane obtained in step 4). The test results are shown in FIG. Figure 2 shown.
[0109] from Figure 2 It can be seen that the composite high-temperature proton exchange membrane provided by the present application provides additional binding force for the phosphoric acid molecules due to the abundant hydrogen bonds in the hydrogen-bonded organic framework material, thereby significantly slowing down the loss rate of phosphoric acid in the composite membrane.
[0110] Performance Test 5
[0111] The H of the high temperature proton exchange membrane in Examples 1 to 6 and Comparative Examples 1 to 2 was tested respectively. 2 / O 2 Fuel cell performance (test object is the proton exchange membrane obtained in step 4), the test results are shown in Table 3.
[0112] Table 3
[0113] Examples <![CDATA[Peak power density (mW cm -2 )]]> Example 1 782.8 Example 2 628.1 Example 3 682.2 Example 4 728.9 Example 5 599.3 Example 6 639.9 Comparative Example 1 428.2 Comparative Example 2 412.9
[0114] As can be seen from Table 3, the ultra-high specific surface area of the hydrogen-bonded organic framework material provides a huge storage space for phosphoric acid molecules, thereby improving the proton conduction performance of the composite membrane and further improving the H 2 / O 2 Fuel cell performance.
[0115] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. An acid-base composite high-temperature proton exchange membrane, characterized in that: The acid-base composite high-temperature proton exchange membrane is formed by cross-linking a carboxyl-containing hydrogen-bonded organic framework material and polybenzimidazole acid-base, and then soaking in phosphoric acid; The carboxyl-containing hydrogen-bonding organic framework material is selected from one of the structures shown in Formula I-1, Formula I-2, Formula I-3, and Formula I-4; 2. The acid-base composite high-temperature proton exchange membrane according to claim 1, characterized in that: The mass ratio of the carboxyl-containing hydrogen-bonding organic framework material to polybenzimidazole is 3:97 to 21:
79.
3. The method for preparing the acid-base composite high-temperature proton exchange membrane according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: (1) ultrasonically dispersing a mixture of a carboxyl-containing hydrogen-bonded organic framework material, polybenzimidazole, and a solvent to obtain a casting solution; (2) The cast membrane is hydraulically pressed onto the surface of the substrate by a doctor blade method, dried, and soaked in phosphoric acid to obtain the acid-base composite high-temperature proton exchange membrane.
4. The preparation method according to claim 3, characterized in that: In the casting solution, the sum of the mass fractions of the carboxyl-containing hydrogen-bonded organic framework material and the polybenzimidazole is 2.5-10%.
5. The preparation method according to claim 3, characterized in that: The solvent is selected from at least one of N,N-dimethylacetamide, N,N-dimethylformamide and dimethyl sulfoxide.
6. The preparation method according to claim 3, characterized in that: The ultrasonic dispersion time is 4 to 12 hours.
7. The preparation method according to claim 3, characterized in that: The substrate is a glass substrate.
8. The preparation method according to claim 3, characterized in that: The drying temperature is 50-80°C.
9. The preparation method according to claim 3, characterized in that: The soaking temperature is 60-100° C., and the soaking time is 2-4 days.
10. Use of the acid-base composite high-temperature proton exchange membrane according to any one of claims 1 to 2 in a fuel cell, characterized in that: The working temperature of the acid-base composite high-temperature proton exchange membrane is 100-200°C.
Citation Information
Patent Citations
Metal-organic framework (MOF) modified graphene / polymer hybrid proton exchange membrane and preparation method thereof
CN104672481A
Amino-functionalized polymer hybrid proton exchange membrane with modified rod-shaped metal organic framework and preparation method of polymer hybrid proton exchange membrane
CN106876759A
Dye and metal organic framework material and preparation method and application thereof
CN109585887A
Mesoporous hydrogen bond organic framework fiber composite material and preparation method and application thereof
CN111636208A
Phosphoric acid doped porous polybenzimidazole electrolyte membrane, preparation method and application thereof
CN112063010A